A Psychological Thriller in Donna Tartt’s the Goldfinch - Abu Fanani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2015)
In this article, the researcher analyzes a psychological thriller in the form of anxiety in Donna Tartt’s the Goldfinch. The researcher then uses psychological theory. The researcher analyzes the main character that undergoes a psychological worry; anxiety. At last, the researcher draws conclusion that the main character, Theodore Decker undergoes recurrent recollection(s), feeling humiliated, worry, fear, nightmares, and feelings of terror.